Gastrointestinal Problems in HIV/AIDS Patients - Zulkhairi Zulkhairi; Imelda Rey; Taufik Sungkar; Lukman Hakim Zain (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2013)
Background: Gastrointestinal (GI) and hepatobiliary disorders are the most common complaints in patients with HIV/AIDS disease. These fundamental problems have not yet been addressed and remains a rewarding area for research. Data about the problems are scarce, especially in Indonesia. This study was aimed to identify gastrointestinal problems in HIV/AIDS patients who were hospitalized in Adam Malik Hospital, Medan.Method: A descriptive study was conducted based on medical records data from non-ambulatory HIV/AIDS patients who had GI problems and who were hospitalized in Internal Medicine wards of Adam Malik Hospital,Medan from 2010-2012. Spearman rank test was used to evaluate the correlation between CD4 level and GI problems among 68 patients with CD4 data.Results: We found 647 HIV/AIDS patients, i.e. 524 (80.9%) male and 123 (19.1%) female patients. Gastrointestinal problems were found in 315 (48.7%) patient among them. Oral candidiasis was the mostcommon case found in 306 (97.1%), which was followed by chronic diarrhea 73 (23.2%), oral candidiasis with chronic diarrhea 64 (20.3%), dyspepsia 22 (6.9%), non-cirrhotic ascites 20 (6.3%), acute diarrhea 8 (2.5%), hepatomegaly 8 (2.5%), dysphagia 6 (1.9%), chronic hepatitis C virus 6 (1.9%), chronic hepatitis B virus 4 (1.3%), GI bleeding 3 (0.9%), and acute hepatitis A virus 1 (0.3%). Unfortunately, we found that therewas only 68 data of CD4. Results of statistical tests showed a significant correlation between CD4 level and gastrointestinal problems (p = 0.04).Conclusion: Oral candidiasis is the most common gastrointestinal problems in HIV/AIDS patients hospitalized in Internal Medicine Wards of Adam Malik Hospital.Keywords: gastrointestinal, HIV/AIDS, oral candidiasis,CD4